Epidemiologic Evaluation of Maxillofacial Trauma in Alzahra Hospital, Isfahan - Abbas Haghighat; Sobhan Pourarz; Afsaneh Zarghami (Shahrekord University of Medical Sciences, 2020)
Background and aims: This study aimed at analyzing the epidemiological features and complications of different types of maxillofacial traumas in patients who referred to Alzahra hospital, Isfahan during 2005-2019.   Methods: This descriptive-analytical cross-sectional study included all patients with maxillofacial traumas who had been admitted to Alzahra hospital from March 1, 2005 to February 31, 2019. Several parameters were registered, consisting of patients' demographic information, and time, location and the etiology of the accident, and clinical details related to injury and treatment procedures were recorded as well. Finally, the data were analyzed using chi-square and Fisher exact tests, and P < 0.05 was considered statistically significant.   Results: A total of 1677 documents of traumatized patients were evaluated, including 79.66% men (n=1336) and 20.33% women (n=341). The statistical difference between the number of male and female patients was significant (P < 0.001) and maxillofacial traumas were more prevalent in the third decade of life (35.4%). Eventually, the highest number of referents was from Isfahan province (79.2%).   Conclusion: In general, traumatic accidents related to face and jaws are more prevalent in 21-30-year-old male patients mostly due to driving accidents, and driving accidents with vehicles was the most frequent cause of trauma.